Penerjemahan Isi Kitab Bulugul Maram Tentang Lima Hadis Pada Bab Targib Fī Makārimi Al-Akhlaq ke dalam Bahasa Indonesian Melalui Perspektif I’rab - Mahirah, Siti Khansa; Yanti, Alfa Auza; Zulaiha, Fitri Nur; Milah, Aang Saeful (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Hadith is one of the religious texts that is important to study and serve as a guide to human life. However, hadiths generally use Arabic which makes translation for non-users of that language necessary. The Bulughul Maram Book, as one of the books containing these thematic hadiths, has a literal translation, but no study of its translation into Indonesian from an i'rabic perspective has been found. The aim of this research is to analyze in depth how i'rab influences word choice, sentence structure and meaning of the original text in the translation process into Indonesian. The research method used is a qualitative method using two data collection techniques, namely library study techniques and text analysis. The conclusion of this research is that there are implications between the faithful translation method and the i'rab perspective regarding a translation that is faithful to the structure and original meaning of the hadith text.